Uso de curso masivo abierto en línea en la enseñanza de las matemáticas - Remache Coyago, Abel Polivio (2017)
In this exploratory work a research was conducted to determine whether a virtual platform with a customized learning content could helps increase the dedication of the students in the field of Mathematical Analysis II. To do so, weekly student activity data was collected, both inside and outside the classroom, for a period of 11 weeks starting on March 10 until May 25 (2014). The scope and purpose of this research is to measure the number of hours spent by students on the system; this information will allow to compare with dedication’s averages published by other authors, e.g. Garmendia, Guisasola, Barragués and Zuza (2006) study found that for a subject with a time allocation four hours a week, students spend an average of 3.28 hours independently, resulting in an average of 7.28 hours total study of matter per week.